Elimination of Negative Stigma through the Use of Media Technology by Librarians with Blind Disabilities - Sabarina, Gustiana; Valentino, Rahmat Alifin; Ramdani, Alwan Husni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research examines the efforts of librarians with visual disabilities to remove negative stigma from society. Research focus on the use of technological media by librarians with visual disabilities to eliminate the negative stigma towards blind people who are considered unable to use technological media. Previous studies agree that every librarian's activities require visual support in all their work. The use of technological media by librarians with disabilities is a social construction of technology as an effort to change social relations in society. This research aims to find out how the use of technological media by librarians with visual disabilities in eliminating the negative stigma. This research uses a qualitative methodology with a case study approach. Data collection techniques include observation and interviews. The data obtained is explained through the stages of data reduction, data presentation and verification. Librarians with visual disabilities have the skills to operate technological media with the help of special software for blind people. Skills in using technological media are demonstrated to users who come to the library. Skills in using technological media supported by special software are demonstrated by blind librarians to users with the aim of changing the negative stigma that assumes that people with disabilities cannot use technological media in their activities. The use of technological media by librarians with disabilities is a socio-technological construction and an adaptation strategy to change their relationship with the social environment.